Classification model for muslimah clothing / Thuraiya Budah @ Udah - Budah @ Udah, Thuraiya (2005)
This research is conduct to address the classification clothing for muslimah. .This study will focus on the classification of fabric and women clothing, to construct the classification model of muslimah clothing. At the first stage of the study, it will discuss about the fabric and women clothing area that will contribute to identify the muslimah clothing area after the muslimah dress code is being analyzed. At the next stage, it will identify the element of women clothing and fabric classification. Furthermore, this study will use taxonomy approach to construct muslimah clothing classification using Maple 6.0 software, which organized the muslimah clothing in hierarchical trees. This classification can be proposed in muslimah clothing recommendation system